The impact of cultural representation of youth on political representation - Battenfeld, Mary (Frontiers in Political Science, 2025)
This essay draws on theories of political philosopher Hanna Pitkin and cultural studies scholar Stuart Hall to consider youth representation in terms of relationships between cultural representation and political representation. I argue that the ways in which youth are represented and misrepresented in cultural discourse and media affects their political representation. After an opening section focused on the problem of cultural misrepresentations of youth, the essay explores concepts of youth and adolescence as they evolved after World War II. The third section assesses the impact of cultural constructs of youth on political representation by reviewing evidence on mainstream media representations of young climate change activists. The essay’s final section analyzes debates related to minimum voting age requirements, and what they suggest about understanding the problem of youth representation.